Thermal Activities In Natural-Oil And Synthetic Lubricants With TiO2 Additives - Abdul Muein, Noor Shafiatul Akmal (Universiti Sains Malaysia, 2022)
The transportation and industrial sectors' reliance on petroleum-based products may pose a threat to future energy security. On occasion, these compounds were returned to the environment, resulting in severe contamination and threats to the environment. Bio-based lubricants are gaining popularity as viable substitutes for mineral-based lubricants since they play an essential role in resolving the issues. It has been discovered that bio-based lubricants are superior to conventional mineral lubricants in terms of lubricating properties, with renewability and biodegradability being their most favourable traits. It is crucial to evaluate the available literature in order to investigate the prospective uses of bio-based lubricants. The objective of this study is to highlight the potential of bio lubricants for a wide range of applications based on research published in peer-reviewed publications over the past decade. This study also highlighted the several applications for which the potential use of bio-based lubricants has been investigated. On the basis of the basic findings, it is possible to infer that bio-based lubricants are a viable alternative to petroleum-based lubricants for a variety of applications due to their extensive availability of qualities required for specific applications. To overcome constraints such as poor low-temperature properties and oxidative stability, chemical modification is required for some applications. With the right composition of base oil and additives, bio-based lubricants can outperform traditional lubricants.